The Routledge Handbook of Second Language Acquisition and Technology - Ziegler, Nicole; González-Lloret, Marta (Taylor & Francis, 2022)
Technology- mediated language learning has matured over the past few decades, with various tools and contexts now widely used in language education for all ages and levels. Many of today's language learners have experienced technology as an ever- present feature both within and beyond the classroom, highlighting how the role of technology has expanded into many daily activities, and underscoring how research in Second Language Acquisition (SLA) can inform and support the use of established and emerging technologies. The role of technology in language learning has continued to grow, with the recent COVID- 19 global pandemic further demonstrating the potential contributions of technology for supporting and facilitating second language development. Answering this increasing interest, this Handbook provides students, teachers, and scholars with a comprehensive collection of chapters on foundational topics and key issues related to technology, SLA, and where relevant, pedagogical applications.